Ekstrak Etanol Kopi Hijau Arabika (Coffea arabica L.) sebagai Antihiperglikemi pada Mencit (Mus musculus) - Hamdani, Irawati; Nurman, Salfauqi (Jurnal Kefarmasian Indonesia, 2020)
Diabetes mellitus is an excessive level of blood sugar concentration disease. One of the compounds that can moderate the blood sugar level is chlorogenic acid that mostly found in green coffee. This study aims to determine the extract activity of Arabica (Coffea arabica L.) green coffee in decreasing the blood sugar level of mice (Mus musculus) that induced by alloxan monohydrate. The method is True Experimental Laboratories with the analysis of chlorogenic acid levels using a UV-Vis spectrophotometer. The research design is Post Test Control Group Design, using 24 mices that divided into six treatment groups. The groups consist of negative control (distilled water), Dose I (100 mg/kg bw), Dose II (200 mg/kg bw), Dose III (300 mg/kg bw), Dose IV (400 mg/kg bw), and positive control (metformin). Blood sugar levels of the mice is measured at the intervals of 1st day, 7th day, 21st day. The data is analyzed using the SPSS program with normality tests (Kolmogorov-Smirnov), homogeneity tests (Levene Test), and parametric statistical tests (One-Way ANOVA). The data results was normally distributed and homogeneous (P> 0.05) with several pairs of data in the treatment group were significantly different (P> 0.05). The extract of Arabica (Coffea arabica L.) green coffee contained 4.235% chlorogenic acid, could reduced the hyperglycemia mice blood sugar levels by the dose of 10.72% (Dose I); 19.85% (Dose II); 27.20% (Dose III); and 31.60% (Dose IV) with dose IV as the effective dose.